2017
DOI: 10.2135/cropsci2016.05.0331
|View full text |Cite
|
Sign up to set email alerts
|

Spelt: Agronomy, Quality, and Flavor of Its Breads from 30 Varieties Tested across Multiple Environments

Abstract: Spelt (Triticum aestivum L. ssp. spelta) is an old hulled wheat currently receiving renewed interest of consumers, bakers, millers, and farmers. Our objectives were (i) to assess the genetic variability and heritability of agronomic and quality traits together with the flavor and odor of breads, (ii) to investigate correlations among these traits, and (iii) to draw conclusions for spelt breeding targeting improved yield, quality, and flavor of end products. Therefore, we investigated 30 spelt varieties in up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
3
14
0
1
Order By: Relevance
“…A weak but significant correlation was found between GI and dough stability ( r = 0.596), which clearly indicated that dough stability was influenced by gluten quality, not quantity. Rapp et al (2017) also demonstrated that the quality of dough made from spelt flour was not correlated with gluten quantity, but it was significantly correlated with GI. The inference is that the quality of spelt gluten is lower than the quality of common wheat gluten.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A weak but significant correlation was found between GI and dough stability ( r = 0.596), which clearly indicated that dough stability was influenced by gluten quality, not quantity. Rapp et al (2017) also demonstrated that the quality of dough made from spelt flour was not correlated with gluten quantity, but it was significantly correlated with GI. The inference is that the quality of spelt gluten is lower than the quality of common wheat gluten.…”
Section: Resultsmentioning
confidence: 91%
“…Spelt is a high-yielding crop in organic farming systems (Żuk-Gołaszewska et al 2015). Breeders are under mounting pressure to develop new spelt varieties that can be effectively grown in various systems with the use of modern technologies that are suitable for industrial processing and that meet consumer expectations (Rapp et al 2017). The growing popularity of spelt can be attributed to its resistance to environmental stressors and relatively low soil requirements.…”
mentioning
confidence: 99%
“…The revived interest in spelt can be attributed to the high nutritional value of its grain, which is rich in protein, macronutrients and micronutrients [38][39][40][41][42][43][44][45], resistance to fungal pathogens [18,[46][47][48][49][50][51], and higher adaptability to varied environments and simplified farming systems in comparison to bread wheat [52][53][54]. The milling quality of spelt grain has been recently investigated by Wiwart et al, Rapp et al,and Sobczyk et al [44,45,55]. The suitability of ancient wheats, including spelt, for the production of functional foods has been discussed by Arzani and Ashraf [26].…”
Section: Discussionmentioning
confidence: 99%
“…Longin et al [43] observed a significant negative correlation between grain yield and protein content in bread wheat, durum wheat, spelt, and emmer, where the corresponding values of the correlation coefficient were determined at: −0.87 (p < 0.001), −0.58 (p < 0.05), −0.83 (p < 0.01), and −0.71 (p < 0.01), respectively. Highly significant negative correlations between hulled yield and protein content (r = −0.60, p < 0.001) were observed in 30 contemporary varieties and breeding lines of winter spelt in six locations in Germany [45].…”
Section: Groupmentioning
confidence: 96%
See 1 more Smart Citation